Tourists’ Perceptions Towards Packaged Tours - Bhaskar Rao, M. (Indian Journal of Marketing, 2007)
Tourism is basically a service industry and is an amalgamation of both tangible and intangible components like accessibility, amenities, attraction, accommodation and activities. The socio-economic implications of tourism include – a) enhancement of domestic and foreign exchange growth, b) employment generation, c) cultural assimilation and d) support to the local people. For tourists, India is a confluence of modernity and traditional hospitality.The organization of a tour can be divided into a) package tours and b) non-package tours. Package tours is a comprehensive programme of tour arranged by a single institution which takes care of the interests of tourists in terms of accessibility, amenities, attractions, accommodation and activities. Package tour is a kind of single window service of a tour. A non-package tour on the other hand, is a tour organized in isolation and planned according to individualized tourist activities.